2018
DOI: 10.1186/s12934-018-0998-4
|View full text |Cite
|
Sign up to set email alerts
|

Widespread effect of N-acetyl-d-glucosamine assimilation on the metabolisms of amino acids, purines, and pyrimidines in Scheffersomyces stipitis

Abstract: BackgroundFollowing cellulose, chitin is the most abundant renewable resource and is composed of the monomeric amino sugar N-acetyl-d-glucosamine (GlcNAc). Although many yeasts, including Saccharomyces cerevisiae, have lost their ability to utilize GlcNAc, some yeasts are able to use GlcNAc as a carbon source. However, our understanding of the effects of GlcNAc on the intracellular metabolism of nitrogen-containing compounds in these yeast species is limited.ResultsIn the present study, we quantitatively inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Total RNA was extracted from the cells harvested at 48 h fermentation using the NucreoSpin RNA (Macherey–Nagel, Düren, Germany) according to the manufacturer’s instructions. The expression levels of ARO4 and ARO7 genes were quantified by real-time PCR as previously described ( Inokuma et al, 2018 ). All the primers used for qRT-PCR are listed in Supplementary Table S1 .…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted from the cells harvested at 48 h fermentation using the NucreoSpin RNA (Macherey–Nagel, Düren, Germany) according to the manufacturer’s instructions. The expression levels of ARO4 and ARO7 genes were quantified by real-time PCR as previously described ( Inokuma et al, 2018 ). All the primers used for qRT-PCR are listed in Supplementary Table S1 .…”
Section: Methodsmentioning
confidence: 99%
“…It was reported that Scheffersomyces stipitis uses N ‐acetyl‐ d ‐glucosamine (GlcNAc) as its sole carbon source, but the GlcNAc metabolic pathway in S. stipitis is still poorly understood. In order to investigate the metabolic responses to GlcNAc in S. stipitis , Inokuma et al conducted both cationic and anionic analyses on a CE‐MS system with sheath‐liquid interface [38]. The harvested yeast cells were first subjected to anaerobic fermentation for 24 h prior to metabolite extraction using a boiling ethanol method at 95°C for 5 min.…”
Section: Applicationsmentioning
confidence: 99%
“…Organic acids were analysed using high-performance liquid chromatography (Shimadzu LC-10AD) as described previously (Mohd Yusoff et al 2012). Ammonia concentration in WSS supernatant was measured using ammonia assay kit (Wako, Japan) (Inokuma et al 2018). Each assay was conducted at least in triplicate.…”
Section: Methodsmentioning
confidence: 99%